Substitution of banana (Musa acuminata L. ev cavendishii) flour for the production of cake-like muffins - Gaviola, Gilly Marie B. (2010)
The study aimed to use banana flour as substitute to all-purpose in the production of cake-like muffins. Substitution of 20%, 30% and 40% banana flour from the total flour content of the adapted recipe was conducted. The products of the three formulation were subjected to Preference Ranking Test. to identify the most preferred formulation and to serve as the final product. Results of the sensory evaluation revealed that the product of the 20% banana flour substitution was the most preferred among the three samples. Results were significantly different from each other at 95% level of confidence through the Friedman's Test. Hence, the cake-like muffin with 20% banana flour was further subjected Consumer Acceptability Test using 9-o=point Hedonic Scale Rating. Based on the mode of responses, the final product was very much liked by the consumers in ters of its appearance, texture, flavor, aftertaste and overall acceptability. Further its desirable physical properties include brown-colored, rounded body and bell-shaped top with an average volume of 112 cm3 and a uniform cell structure. Moreover , the product contains approximately 0.58% crude fiber, 17.52% moisture and Aw of 0.84. Being an intermediate moisture food (IMF), it can be packed in polyethylene (PP) bags to preserve its quality for a longer period of time.